Effects of the antidepressants desipramine and fluvoxamine on latency to immobility and duration of immobility in the forced swim test in adult male C57BL/6J mice. Issue 5 (August 2018) - Koek, Wouter; Sandoval, Thomas L.; Daws, Lynette C.
Abstract : The forced swim test in rodents allows rapid detection of substances with antidepressant-like activity, evidenced as a decreased duration of immobility that is produced by the majority of clinically used antidepressants. Antidepressants also increase the latency to immobility, and this additional measure reportedly can increase the sensitivity of the forced swim test in mice. Extending these findings, the present study examined the effects of desipramine and fluvoxamine in a forced swim test in C57BL/6J mice, a strain commonly used as background for genetic modifications, analyzing results with a method (i.e. survival analysis) that can model the skewed distribution of latencies and that can deal with censored data (i.e. when immobility does not occur during the test), in comparison with the more traditional Student's t -test. Desipramine increased the latency to immobility at 32 mg/kg, but not at lower doses. Fluvoxamine also did not affect latency at lower doses, but in contrast to desipramine, fluvoxamine decreased the latency to immobility at the highest dose (i.e. 32 mg/kg). At doses affecting latency to immobility, neither desipramine nor fluvoxamine significantly affected duration of immobility. Together, these results are generally consistent with the suggestion that inclusion of the latency measure can increase the sensitivity of the forced swim test to detect antidepressant-like effects in mice.